Surface nitridation of yttria-doped tetragonal zirconia polycrystals (Y-TZP): Microstructural evolution and kinetics - Chung, TJ; Lee, JS; Kim, DY; Song, H (AMER CERAMIC SOC, 1999)
Sintered tetragonal-zirconia polycrystals (TZP) were embedded in a zirconium nitride powder bed and heat-treated at various temperatures. Surface layers of the TZP specimens were transformed to a stabilized cubic-zirconia by nitrogen incorporation, and their thickness was observed to increase by a parabolic rate law. The nitrogen diffusivity was evaluated from the temperature dependence of the nitridation rate. The microstructure of the nitrided layer was composed of different zones of equiaxed and columnar grains. The columnar grains were developed along the nitrogen flux lines. The observed microstructural evolution was explained in terms of nucleation and growth kinetics of nitridation.